2016
DOI: 10.1002/ecs2.1268
|View full text |Cite
|
Sign up to set email alerts
|

Knocking back invasions: variable resistance and resilience to multiple cold spells in native vs. nonnative fishes

Abstract: Extreme climate events can interact synergistically with invasions to dramatically alter ecosystem structure, function, and services. Yet, the effects of extreme climate events on species invasions remain unresolved. Extreme climate events may increase resources and decrease biotic resistance by causing physiological stress and/or mortality of native taxa, resulting in invasion opportunities for nonnative species. Alternatively, extreme climate events may regulate nonnative populations, preventing them from ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…() and in additional headwater mangrove creeks in Everglades National Park (Boucek and Rehage ; Rehage et al. ). Although cold‐induced mortality may moderate some of the ecological impacts by temporarily reducing population sizes of abundant nonnative fishes, these studies also demonstrate the variability of nonnative fish populations that results from their cold intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…() and in additional headwater mangrove creeks in Everglades National Park (Boucek and Rehage ; Rehage et al. ). Although cold‐induced mortality may moderate some of the ecological impacts by temporarily reducing population sizes of abundant nonnative fishes, these studies also demonstrate the variability of nonnative fish populations that results from their cold intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Rehage et al (2016) attribute this spatial variation in resilience to differences in distance to warm water source populations. Likewise, Stevens et al (2016) found that following the 2010 cold spell in Florida, resistance of a tropical estuarine piscivore were similar across three of four estuaries but resilience varied, possibly an effect related to inter-estuary differences in geophysical structuring that may influence reproduction, recruitment, and juvenile survival.…”
Section: Effects Of Landscape Features On Subtropical Community Resismentioning
confidence: 98%
“…For instance, Rehage et al (2016) showed that across eight non-native fish populations affected by the 2010 disturbance, population resilience varied from within one year, to populations that have exhibited no recovery five years post disturbance. Rehage et al (2016) attribute this spatial variation in resilience to differences in distance to warm water source populations.…”
Section: Effects Of Landscape Features On Subtropical Community Resismentioning
confidence: 99%
See 1 more Smart Citation
“…Over the long-term, extreme cold spells contribute to the physiological threshold ranges for native species, and in theory can limit the range expansions of some introduced species. With cold tolerances being one of the main determinants for a species distributional range, there is a chance for the population decline of a non-native species in the event of an extreme climatic event, such as a cold spell (Kreyling et al 2015, Rehage et al 2015. As a result, measuring species' responses to extreme events in addition to the mean changes in climate is necessary to predict species range limits under future conditions (Zimmerman et al 2009).…”
Section: Introductionmentioning
confidence: 99%